Random attractors for a class of stochastic reaction‐diffusion equations on RN with multiplicative noise. Issue 4 (14th June 2019) - Li, Bowen; Jiang, Yong; Li, Xiaojun
Abstract : This paper is concerned on the existence of random attractors for a class of nonautonomous stochastic reaction‐diffusion equations defined on unbounded domains with multiplicative noise. By using Ornstein‐Uhlenbeck process, we transfer the original equation to a random dynamical system and then get the asymptotic compactness of it, which implies the existence of random attractor.